Non-equivalent role of inter- and intramolecular hydrogen bonds in the insulin dimer interface - Antolíková, Emília; Žáková, Lenka; Turkenburg, Johan P; Watson, Christopher J; Hančlová, Ivona; Šanda, Miloslav; Cooper, Alan; Kraus, Tomáš; Brzozowski, A Marek; Jiráček, Jiří (The Journal of biological chemistry, 2011)
Apart from its role in insulin receptor (IR) activation, the C terminus of the B-chain of insulin is also responsible for the formation of insulin dimers. The dimerization of insulin plays an important role in the endogenous delivery of the hormone and in the administration of insulin to patients. Here, we investigated insulin analogues with selective N-methylations of peptide bond amides at positions B24, B25, or B26 to delineate their structural and functional contribution to the dimer interface. All N-methylated analogues showed impaired binding affinities to IR, which suggests a direct IR-interacting role for the respective amide hydrogens. The dimerization capabilities of analogues were investigated by isothermal microcalorimetry. Selective N-methylations of B24, B25, or B26 amides resulted in reduced dimerization abilities compared with native insulin (K(d) = 8.8 μM). Interestingly, although the N-methylation in [NMeTyrB26]-insulin or [NMePheB24]-insulin resulted in K(d) values of 142 and 587 μM, respectively, the [NMePheB25]-insulin did not form dimers even at high concentrations. This effect may be attributed to the loss of intramolecular hydrogen bonding between NHB25 and COA19, which connects the B-chain β-strand to the core of the molecule. The release of the B-chain β-strand from this hydrogen bond lock may result in its higher mobility, thereby shifting solution equilibrium toward the monomeric state of the hormone. The study was complemented by analyses of two novel analogue crystal structures. All examined analogues crystallized only in the most stable R(6) form of insulin oligomers (even if the dimer interface was totally disrupted), confirming the role of R(6)-specific intra/intermolecular interactions for hexamer stability.
Keywords: vodíková vazba; Protein Multimerization; inzulin prasečí; Protein Structure, Secondary; kvarterní struktura proteinů; krystalografie rentgenová; Crystallography, X-Ray; sekundární struktura proteinů; zvířata; Methylation; stabilita proteinů; Swine; metylace; Hydrogen Bonding; Animals; Insulin, Regular, Pork; Protein Structure, Quaternary; Protein Stability; prasata; multimerizace proteinu